Traumatic Haemothorax: Diagnostic approaches and surgical management: diagnostic approaches and surgical management - hussen, waleed M.; Noureldin Abdulkadir, Ahmed; S. Yuser, Akeel (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Traumatic haemothorax is a collection of blood within the pleural cavity due to a penetrating or blunt injury leading to blood accumulation inside the pleural space with its respiratory and hemodynamic consequences.Objectives: Is to retrospectively study eighty victims of traumatic haemothorax regarding their age, gender, types of injury, and their sequel, as well as the methods of investigation, treatment modality (conservative or operative) and their outcome.  Patients and methods: The data of 80 patients with traumatic haemothorax admitted to Ibn AL-Nnafees teaching hospital from (1st of August 2018 to 30th. of September 2019), was collected. The data was analyzed according to age, gender, clinical features, associated findings, mechanism of injury, imaging, procedure performed, operative finding, post-operative outcome, morbidity, mortality and follow up.Result: Seventy-four (92.5%) of our patients were males, and 32 (40%) were between 21-30 year of age. Fifty-four patients (67.5%) were injured by bullet, stab or shell injury. The remaining 26 patients (32.5%) were affected by blunt injury. Sixty patients (75%) were treated successfully with tube thoracostomy only. Eight patients (10%) required emergency thoracotomy after the insertion of chest tube, ten patients (12.5%) needed elective thoracotomy for (clotted haemothorax, foreign body extraction or empyema), and the remaining two patients (2.5%) presented with minimal haemothorax and didn’t need any intervention. Sixty-two of our patients (77.5%) were discharged well within 7 days. Those with air leak or who needed thoracotomy (elective or emergency) had longer hospitalization periods. Only one patient with empyema needed to stay more than 30 days. Sixty-nine (86.3%) of our patients were discharged well, while complication occurred in three patients (3.8%) with air leak, two (2.5%) ended with empyema and four patients (5%) with clotted haemothorax. Two patients (2.5%) died due to sever uncontrolled bleeding.Conclusion: Most of the patients with traumatic haemothorax were simply managed by tube thoracostomy only. In haemodynamically unstable patients, no time should be wasted for investigations and a resuscitative thoracotomy can save the patient’s life. Rapid assessment and early intervention will save the life of patient with traumatic haemothorax.